EVALUASI PERDA NOMOR 6 TAHUN 2011 TENTANG PEMBERANTASAN PELACURAN DI WILAYAH KABUPATEN BATANG - Diah Setyowati; Sulistyowati .; D Ghulam Manar (Journal of Politic and Government Studies, 2013)
ABSTRACTThe purpose of this research is to investigate the implementation of Regulation No. 6 of 2011 on the eradication of prostitution in the district of Batang and see its effectiveness. Variables used to see the implementation of Regulation No. 6 of 2011 are communication, resources, disposition, and bureaucratic structures and to evaluate their effectiveness using indicators of goal achievement, productivity, and efficiency are analyzed qualitatively descriptive look at the phenomenon that is occurred. Looking at the various aspects that have been analyzed can be concluded that the law No. 6 of 2011 on the eradication of prostitution in the district of Batang is not implemented properly and its implementation has not been effective.